(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Quality of work life indicate the degree to which members of a work organization are able to satisfy important personal needs through their experiences in the organization. Organizational commitment reflect employees attitude towards their organization. Present study attempts to find out the relationship between quality of work life and organizational commitment among drivers working in South Tamil Nadu. Data were collected from 204 drivers working in South Tamil Nadu using a two stage sampling procedure. Quality of work life was measured by using the scale developed by Richard E Walton (1975) and organizational commitment was assessed by using the scale developed by Allen and Meyer (1990). Results revealed a significant correlation between the two variables and found a positive relationship between the two. The study while assessing the impact of quality of work life on organizational commitment found that quality of work life is exerting a significant influence on organizational commitment.